Alternative Proposals to Violence: More than a Methodology, a Philosophy for Life - Betancourth Aragón, Zaida Victoria Narcisa (2024)
This theoretical review of the Proposals for Alternatives to Violence (PAV) configures a methodology for debating and working on alternatives to violence, which is nourished by the contributions of popular education and Paulo Freire. The text makes a brief conceptualization of the PAVs in Ecuador, an understanding of violence and the contributions of these the contributions of these proposals for the achievement of a culture of peace. It is The different elements of the PAV methodology (affirmation, assertive listening and communication, cooperative construction, community building) and, in particular, the Transformative Power (PT), which integrates each element of the PAV. In the last part, we present some testimonies of participantsand discuss the and discuss the scope and challenges they define for the currentcontexts of violence in the country.